Utilization of Jackfruit (Artocarpus heterophyllus Lam.) seed flour in gravy production. - Calimpong Elaiza Bito-on (2015.)
The study aimed to develop a chicken gravy formulation using jackfruit seed frlour. Four formulations of chicken gravy (10%, 25%, 50% ND 100%) were produced and underwent sensory evaluation tests. Rank test for preference and general acceptability test were used to determine the Most Preferred Formulation (MPF). Chicken gravy from the MPF was then subjected to physic chemical tests such as determination of pH, total soluble solids, titrable acidity, viscosity, crude fat, and crude protein, and sensory evaluation.
Thesis (Undegraduate. Bachelor of Science in Food Technology) School of Technology, University of the Philippines Visayas. 2025.
Keywords: Seeds -- Jackfruit; Gravy